1982
DOI: 10.1038/ki.1982.186
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical and in vitro erythropoietic responses to androgens in renal failure

Abstract: To assess in vitro erythropoietic cultures as a tool to discriminate between patients whose anemia improves with and those whose anemia fails to improve with androgens, bone marrows of 24 anemic patients receiving maintenance hemodialysis in hormone-depleted plasma clots were cultured. While erythroid colony proliferation in the presence and absence of androgens by cells of seven patients with good clinical outcomes who were initially studied was similar to that of normal donors, it was reduced (P less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Their mechanisms of action in chronic renal failure are not well understood. They do not increase the red-cell survival [3], Preliminary studies showed that androgens produced a rise in the serum erythropoietin activity that was attribut ed to the stimulation of endogenous erythropoietin secre tion [1,4], but these data were not confirmed later [5], perhaps because of the low sensitivity of the assay used. Other studies discovered that androgens produced a di rect stimulation of marrow heme synthesis [6], augmenta tion of growth by differentiated stem cells [7] and enhanc ing the sensitivity of erythroid progenitors to circulating erythropoietin [5, 8.…”
Section: Introductionmentioning
confidence: 95%
“…Their mechanisms of action in chronic renal failure are not well understood. They do not increase the red-cell survival [3], Preliminary studies showed that androgens produced a rise in the serum erythropoietin activity that was attribut ed to the stimulation of endogenous erythropoietin secre tion [1,4], but these data were not confirmed later [5], perhaps because of the low sensitivity of the assay used. Other studies discovered that androgens produced a di rect stimulation of marrow heme synthesis [6], augmenta tion of growth by differentiated stem cells [7] and enhanc ing the sensitivity of erythroid progenitors to circulating erythropoietin [5, 8.…”
Section: Introductionmentioning
confidence: 95%
“…Increases in hematocrit have previously been noted during treatment with fluoxymesterone without an accompanying increase in serum erythro poietin levels [Raich and Korst, 1978], and in vitro studies have suggested a direct stimulatory effect by a variety of androgens on the proliferation of erythroid progenitor cells [Gordon et al, 1970;Gorshein et al, 1974a, b;Paulo et al, 1974;Modder er al., 1978;Peschle et al, 1979;Neff et al, 1981]. Indeed, the abil ity of androgens to stimulate erythroid colony growth from marrow cells of CHD subjects in vitro has been suggested to predict for in vivo clinical responsive ness [Kalmanti et al, 1982].…”
Section: Discussionmentioning
confidence: 99%
“…Though we could not obtain funds for this study, others have subse¬ quently done such studies and indeed in vitro response parallels that in vivo (Kalmanti et al 1982). Deficiency of vitamin 12, folate and iron were treated.…”
mentioning
confidence: 89%